2016
DOI: 10.5194/isprsarchives-xli-b7-789-2016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Spectral, Spatial and Polarimetric Classification of Urban and Periurban Landcover Using Temporal Sentinel – 1 Images

Abstract: ABSTRACT:Landcover is the easiest detectable indicator of human interventions on land. Urban and peri-urban areas present a complex combination of landcover, which makes classification challenging. This paper assesses the different methods of classifying landcover using dual polarimetric Sentinel-1 data collected during monsoon (July) and winter (December) months of 2015. Four broad landcover classes such as built up areas, water bodies and wetlands, vegetation and open spaces of Kolkata and its surrounding re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…This indicates that these Sentinel-1A-derived images, when using their information in a complementary way, can effectively improve classification accuracy. Some previous studies have also reported on the importance of using the coherence and texture information of SAR data [17,19,40].…”
Section: Classification Results Using Different Sentinel-1a-derived Imentioning
confidence: 99%
“…This indicates that these Sentinel-1A-derived images, when using their information in a complementary way, can effectively improve classification accuracy. Some previous studies have also reported on the importance of using the coherence and texture information of SAR data [17,19,40].…”
Section: Classification Results Using Different Sentinel-1a-derived Imentioning
confidence: 99%
“…While the use of exclusively backscattering 37 coefficients yielded an overall accuracy of less than 50% (Roychowdhury, 2016), more 38 accurate classifications have been possible using a combination of Haralik textures, the 39 polarization ratio and the local mean together with the VV backscattering coefficients 40 (Inglada et al, 2016). However, in some areas (including our study area) there were few 41 opportunities to obtain polarimetric Sentinel-1A data.…”
Section: Introduction 20mentioning
confidence: 99%